Eugenol-Based Polyacetylenes: Examining Its Synthesis and Utility - Rahim, E A; Sanda, F (Recent Developments in Chemistry and Biochemistry Research Vol. 8, 2024)
Eugenol (4-allyl-2-methoxyphenol) is the main component (80% by weight) of clove oil found in Indonesia and is widely used as perfumes, antioxidants, medicines, foods, and flavoring. Eugenol is an ingredient of inexpensive nature, containing hydrophilic and allyl phenolic functional groups, and is expected to be a major component of chemical synthesis that has eco-friendly properties. Eugenol is an inexpensive natural ingredient, which contains a functional group of phenolic hydroxyl and allyl and is to be a major component of chemical synthesis which is environmentally friendly. In order to conduct the study, Eugenol 99 % was purchased from Indesso.com Indonesia, [Rh(nbd)2Cl] was purchased from Wako Japan, [Rh+] was synthesized according to the literature. MoCl5 was purchased from Wako Japan. NaOH was purchased from Wako Japan. K2CO3 was purchased from Wako Japan. All Polymers were purified by HPLC. Monomer synthesis and polymer synthesis were synthesized according to the literature. Poly (1) to Poly (3) showed widespread UV-Vis absorption at 300-450 nm and poly (4) showed cotton and UV-vis effects at 400 nm. Solvents and temperatures can tune the helical structure of poly (4). The future of semiconductor materials can serve as smart textiles, lab on a chip, portable compact screens, and skin cancer treatment. With cheap and easy-to-obtain basic materials in Indonesia, this polymer is increasing in price. In the future, the helical polymer will become a very useful material. This material has a good prospect of being developed in Indonesia. It was concluded that Eugenol-based polyethylene can be applied as an electronic plastic and in the pharmaceutical industry. The continuation of research in synthesizing new polymers from eugenol ingredients and developing new functions should be continued.